Digitalization and its impact on commercial banks’ profitability in Vietnam - Huong Mai Nguyen; Huyen Thi Ngoc Pham; Khue Minh Tran; Mai Thi Tuyet Nguyen; Yen Thi Hai Nguyen (Ho Chi Minh City Open University Journal of Science - Economics and Business Administration)
Amid the rapid development of the digital economy in Vietnam, traditional industries, including commercial banking, must recognize digitalization as both a prevailing trend and an essential requirement for sustainable development. This study utilizes the Feasible Generalized Least Squares (FGLS) regression method to examine the impact of digitalization on the profitability of Vietnamese commercial banks from 2013 to 2022. Profitability is measured by Return on Assets (ROA), while the digitalization level is represented by the ICT Index (Information and Communication Technology Development and Application Readiness Index). The model also incorporates two control variables: Credit Risk and Solvency. The findings demonstrate that digitalization has improved profitability in commercial banks. Additionally, credit risk is found to have a negative impact on the profitability (ROA) of commercial banks, while the solvency ratio shows the opposite. Based on these results, the authors propose recommendations to enhance the digitization process and consequently elevate operational efficiency and profitability in Vietnamese commercial banks.